2022
DOI: 10.1038/s41598-022-11617-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting compliance with national accreditation essential safety standards in the Kingdom of Saudi Arabia

Abstract: Accreditation is a widespread culture internationally and nationally. The effectiveness of compliance with accreditation standards was positively correlated with health care settings’ performance in multiple aspects: leadership, professional performance, patient safety and organizational culture. There is limited knowledge of the national compliance rate with accreditation standards. Therefore, it is important to assess the hospital compliance with accreditation rate in the Kingdom Saudi Arabia (KSA) and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
(17 reference statements)
1
13
0
1
Order By: Relevance
“…For-profit service providers and compliance were negatively associated in 29 studies [ 13 , 16 , 32 , 45 , 48 , 52 , 57 , 60 – 62 , 65 , 72 , 74 , 76 , 80 , 84 – 87 , 90 – 93 , 104 , 113 , 115 , 116 , 119 , 123 ], positively associated in seven [ 50 , 58 , 63 , 81 , 95 , 117 , 121 ], with a null association in 17 studies [ 35 , 36 , 47 , 49 , 51 , 54 , 59 , 64 , 71 , 82 , 83 , 103 , 106 , 108 , 118 , 120 , 122 ]. Aligned to the profit motive, in a qualitative study, staff in poorly-performing NHs (as measured by compliance) were instructed to prioritise the admission of people that attracted higher fees [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For-profit service providers and compliance were negatively associated in 29 studies [ 13 , 16 , 32 , 45 , 48 , 52 , 57 , 60 – 62 , 65 , 72 , 74 , 76 , 80 , 84 – 87 , 90 – 93 , 104 , 113 , 115 , 116 , 119 , 123 ], positively associated in seven [ 50 , 58 , 63 , 81 , 95 , 117 , 121 ], with a null association in 17 studies [ 35 , 36 , 47 , 49 , 51 , 54 , 59 , 64 , 71 , 82 , 83 , 103 , 106 , 108 , 118 , 120 , 122 ]. Aligned to the profit motive, in a qualitative study, staff in poorly-performing NHs (as measured by compliance) were instructed to prioritise the admission of people that attracted higher fees [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…Larger facilities and compliance were negatively associated in 40 studies [ 13 , 14 , 16 , 34 – 37 , 46 , 50 – 52 , 54 , 57 , 58 , 60 – 62 , 64 , 74 , 77 , 80 , 82 , 83 , 86 , 91 – 96 , 106 , 113 , 114 , 116 , 117 , 120 , 122 , 124 , 127 , 128 ]; three reported a positive association [ 59 , 63 , 71 ] and 16 a null association [ 45 , 47 , 49 , 72 , 78 , 80 , 81 , 85 , 87 , 97 , 105 , 108 , 118 , 121 , 123 , 126 ] (one study [ 80 ] reported larger size NHs had a null association whereas larger size assisted-living facilities had a negative associat...…”
Section: Resultsmentioning
confidence: 99%
“…For-profit service providers and compliance were negatively associated in 29 studies (13, 30, 40, 45, 46, 49–51, 55, 59, 64, 72, 74, 77, 79, 81, 83, 85, 93, 95, 99, 103–105, 109, 117–120) , positively associated in seven (47, 52, 57, 90, 110, 115, 121) , with a null association in 17 studies. (36, 37, 48, 54, 56, 58, 61, 66, 71, 80, 86, 88, 89, 111, 122–124) Aligned to the profit motive, in a qualitative study, staff in poorly-performing NHs (as measured by compliance) were instructed to prioritise the admission of people that attracted higher fees.…”
Section: Resultsmentioning
confidence: 99%
“…(125) Larger facilities and compliance were negatively associated in 40 studies (13, 15, 35-38, 45-47, 49-51, 53, 57-59, 61, 66, 74, 79, 81, 82, 85, 86, 89, 90, 93, 95, 96, 106, 109, 111, 113, 115, 116, 118, 123, 124, 126, 127) ; three reported a positive association (48,52,71) and 16 a null association. (40,54,56,72,84,88,97,104,105,107,109,110,(120)(121)(122)128) (one study (109) reported larger size NHs had a null association whereas larger size assisted-living facilities had a negative association, thereby represented in both columns). The longer a service was in operation was reported to be associated with poorer compliance in four of five studies.…”
Section: Structural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation